Are metacognitive processes associated with posttraumatic stress symptom severity following acquired brain injury?. (14th July 2014) - Gill, Ian J.; Mullin, Stephen; Simpson, Jane
Abstract: Purpose : Although posttraumatic stress disorder (PTSD) after acquired brain injury (ABI) is relatively common, its causal mechanisms remain speculative and little research has considered psychological perspectives. The current study aimed to examine whether metacognitive variables were associated with posttraumatic stress symptom (PTSS) severity in individuals with an ABI. Methods : Participants who had a traumatic brain injury ( n  = 47) or subarachnoid haemorrhage ( n  = 93) completed questionnaires related to demographic, clinical, social support and metacognitive variables. Correlation analyses and a hierarchical multiple regression analysis, with total PTSS severity used as the outcome variable, were conducted. Results : Results demonstrated that metacognitive factors were correlated with PTSS severity and were able to explain an additional and significant amount of variance in PTSS severity within the regression analysis. Conclusions : The results provide preliminary support that metacognitive variables are associated with PTSS after ABI. Clinical implications within rehabilitative settings are discussed, as well as theoretical and research implications in the context of the study's limitations. Implications for Rehabilitation: Posttraumatic stress disorder (PTSD) can impede quality of life after brain injury. Clinical, social and metacognitive processes all influence the development of PTSD after brain injury and should be considered within rehabilitative care plans. Rehabilitative care plans should incorporate interventions for PTSD when appropriate, and metacognitive interventions could prove beneficial.